A new species of driftwood catfish Centromochlus Kner, 1858 (Siluriformes, Auchenipteridae, Centromochlinae) from Tocantins-Araguaia River drainage - Coelho, Fernanda L.; Chamon, Carine C.; Sarmento-Soares, Luisa M. (Zootaxa, 2021)
The genus Centromochlus includes eight catfish species in the Amazon and Orinoco river systems: C. schultzi from Xingu and Tocantins-Araguaia rivers; C. melanoleucus from Tapajós and Teles Pires rivers; C. macracanthus from Negro River; C. orca from Nhamundá River; C. heckelii and C. existimatus from Amazon and additionally at the Essequibo rivers; C. carolae and C. musaica from Orinoco River system. Recent field expeditions and collection examination revealed an undescribed species of Centromochlinae that has compatible features with Centromochlus. We herein describe a new species of Centromochlus from the Tocantins-Araguaia River drainage, diagnosed among most Centromochlinae by having a vermiculated color pattern on the dorsum and included in Centromochlus by sharing the derived features: ventrolateral position of eye socket; sphenotic notched for the exit of infraorbital canal; and posterior serrations along pectoral-fin spine numerous. The new species is diagnosed from congeners by having the pectoral-fin spine with dark bars, alternating with light bars (vs. pectoral-fin spine with light and uniform color in all Centromochlus); and it is further distinguished from its congeners (except C. carolae) by the ventral surface of head moderate to largely pigmented (vs. ventral surface of head unpigmented in C. heckelii, C. existimatus, C. orca, C. musaicus, C. schultzi, with few scattered dark chromatophores in C. macracanthus and C. melanoleucus; see diagnosis). A discussion about the systematics of the genus, plus the conservation status of the new species, and an identification key to species of Centromochlus, are also provided.